IMPLEMENTASI BIMBINGAN AGAMA TERHADAP KESEHATAN MENTAL DAN FISIK DALAM UPAYA PENCEGAHAN WABAH COVID-19 - AL Fahmi, Faiz Fikri; Firdiyani, Fitria (ISLAMIKA, 2021)
The practice of religious teachings, apart from being able to provide curative therapy, also has a preventive aspect to mental or mental disorders. In religion, mental health is a person's ability to manage psychological functions so as to create a good adjustment between himself, both with other humans, other living creatures, the environment, the universe and with God dynamically based on the Qur'an. and Hadith. So by practicing religious values ​​in daily life, problems related to the Covid-19 outbreak and mental health can be resolved. Basically, the purpose of religion is to determine a person to accept the reality of life that has been arranged by God. Therefore it can also be said that religion has a function on physical and mental health which is very important in human life, without religion it is impossible for humans to feel happiness and peace of life. Without religion, it is impossible to foster a safe and peaceful atmosphere. Keywords: Religion, Mental Health, Physical Health, Covid-19 Pandemic